Tinjauan Yuridis Tindak Pidana Penggelapan (Studi Putusan No. 9/Pid.B/2016/PN. Medan) - Abdi Azkhari Butar Butar; Abdul Lawali Hasibuan; Wessy Trisna (Universitas Medan Area, 2020)
The rise of theft, loss and embezzlement of motorbikes in the city of Medan is never ending even no longer a public secret, every day there are always reports of motorcycle loss in the Old Deli Police Station for that the writer feels interested in doing a study about the theft of the motorcycle. The method used in this study is normative juridical and analytical descriptive. Judge's consideration in examining cases of embezzlement has incriminating and mitigating matters. The aggravating thing is that the Defendant's actions can disturb the community and the mitigating thing is that the Defendant admitted frankly his actions and regretted them and the Defendant has never been punished. Efforts made by law enforcers against motorcycle embezzlement are preventive measures, which are efforts that prevent acts or criminal offenses occurring both institutionally and in coordination with the local community. While other efforts are repressive efforts, namely efforts that are emphasized in the criminal process against the perpetrators after the crime occurred, so that it creates a deterrent effect on the perpetrators so that they do not commit-another-crime